Appraising science-policy interfaces in local climate change policymaking: Revealing policymakers’ insights from Izmir Development Agency, Turkey - Eroğlu, Mehmet; Öğüt Erbil, Aslı (Elsevier, 2022)
Developing knowledge-based and usable climate change policies requires establishing science-policy interfaces through which knowledge producers and policymakers cooperate. Current research reveals that co-production- based interfaces dominated neither by knowledge producers nor policymakers succeed in facilitating the transformation of knowledge into politics. From this point of view, this paper explores how Izmir Development Agency (IZKA), a regional development agency in Turkey, utilizes scientific knowledge and science-policy interfaces in its activities on climate change. Based on the analysis of agency documents and semi-structured interviews with experts from and outside IZKA, the findings indicate that IZKA thrives in integrating scientific knowledge on climate change in its activities drawing from multi-stakeholder and multi-level science-policy interfaces that have significant similarities with the co-production model. In these interfaces, international, national, regional, and local stakeholders share their resources, knowledge, and experience on climate change. Although legal, geographical, and demographic conditions also have an impact, the main reason behind IZKA’s success is the agency’s climate-focused vision that shapes decisions, strategies, organizational structure, and activities. In parallel to the indicated finding, this paper also discloses that the perspective of not prioritizing climate change and considering the potential benefits as only “co-benefit” does not yield results with the desired efficiency. Another finding is that even though the national government is the main actor on climate in Turkey, development agencies are capable of carrying out transformative activities in their regions, albeit limited.
Keywords: climatic changes; policy sciences; Izmir Development Agency; environmental policy